Coordination for the Eradication of Violence Against Women in the District of Villa El Salvador 2019-2021 - Reyes Allpoc, Karla Paula (2023)
This study critically analyzes the strategies implemented by the District Coordination Instance (IDC) of Villa El Salvador to prevent, sanction, and eradicate violence against women. It employs a mixed approach, combining qualitative documentary analysis and interviews with key actors, with a quantitative component through a Likert questionnaire applied to IDC members. Its objectives are: a) To analyze the IDC's intersectoral management model against gender-based violence, b) To identify management tools and concrete actions developed, and c) To evaluate the impact of the participation of women's organizations. Tools such as district plans have enabled the implementation of local public policies, while training programs have strengthened capacities and promoted cultural changes.The study concludes that the IDC has consolidated an effective model based on intersectoral articulation, active participation of actors, and empowerment of women's organizations, contributing to more equitable and violence-free societies. This experience sets a valuable precedent as a model for other similar instances.